Down streaming Research through Community Assistance in the Development of Archimedes Turbine Low Flow Micro Hydro Power Plants in Rural Areas - Sarjito, S; Annas Wirawan , Fauzan; Kurniawan , Sidik; Dwi Nugroho , Bagus (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2024)
The purpose of this community service is to disseminate research results regarding the application of microhydro energy power plants with the Archimedes Turbine system which is suitable for application in rural areas because it only requires a small water discharge. The socialization and dissemination process was carried out by establishing partners in Tliu village, East Amanuban, South Central Timor. The research was carried out in order to optimize the design of the Archimedes Turbine type by engineering the optimal spacing of turbine threads, the number of turbine blades and the slope of the turbine blades. The results of the research were disseminated to provide an overview of the prospects for an alternative Archimedes Turbine power plant to support daily activities in an area where until now electricity has not been fully enjoyed by the people of Tliu, East Amanuban, South Central Timor.